THE TALIBAN & AFGHANISTAN: CONFLICT & PEACE IN INTERNATIONAL LAW PERSPECTIVE - Amini, Ma'ruf; Arifani, Devina (UNISSULA, 2021)
This study aims to determine the political situation in Afghanistan which is now occupied by the Taliban. This qualitative research method is often called